2022
DOI: 10.54986/irjee/2022/jan_mar/73-80
|View full text |Cite
|
Sign up to set email alerts
|

Use of Face Masks in India During COVID-19 : An Exploration of the Behavioral Tendencies of Mask Users

Abstract: Covid-19 has necessitated mask use to safeguard oneself from coronavirus. The mask usage and safety practices followed by the public in India are reported in this paper. Sixty per cent of the subjects purchased masks on their own while 19 per cent stitched their masks; masks were used regularly (76%) for less than 4 hours (64.22%). During the lockdown, at workplaces, masks were removed for less than 30 minutes per day. Subjects reported that safety feeling was experienced when masks were donned (87%); felt tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The similar trend was observed in the present study that there is no significant relationship between the age or gender of the study subjects and knowledge of mask disposal. However, the study conducted by Soni et al showed a positive association between the age of the respondents belonging to the age group of 19-28, 29-38, and 39-48 years were more vigilant and carefully followed safety measures in handling masks [11].…”
Section: Discussionmentioning
confidence: 95%
“…The similar trend was observed in the present study that there is no significant relationship between the age or gender of the study subjects and knowledge of mask disposal. However, the study conducted by Soni et al showed a positive association between the age of the respondents belonging to the age group of 19-28, 29-38, and 39-48 years were more vigilant and carefully followed safety measures in handling masks [11].…”
Section: Discussionmentioning
confidence: 95%